Physicochemical Classification and Formulation Development Of Solid Dispersion Of Poorly Water Soluble Drugs: An Updated Review - Giri, Tapan Kumar (International Journal of Pharmaceutical & Biological Archive, 2010)
It is commonly recognized in the pharmaceutical industry that more than 40% newly discovered drug candidates are poorly water soluble. The solubility behaviour of drugs remains one of the most challenging aspects in formulation development and also complicating the delivery of poorly water soluble drugs. To improve such poor solubility issues, solid dispersion techniques are widely applied to increase the apparent solubility or enhance the oral bioavailability of poorly water soluble drugs. Inspite of tremendous potential for improving drug solubility, only few products have been marketed since the development of this technology 40 years ago. This article begins with various types of solid dispersion systems including simple eutectic mixture, solid solutions, glass solutions, and amorphous precipitation in a crystalline carrier. The remaining portion of this article is devoted to the various formulation and development techniques for solid dispersion.